Translating Urban/Translating Ritual: An Ethnographic Study of Dev Uthan Ekadashi - Dhandhi, Muskan; Sigroha, Suman (Text Matters: A Journal of Literature, Theory and Culture, 2025)
Gurugram—a city located near Delhi, in the state of Haryana—is an important contributor to the country’s information technology, finance, and banking sectors. Geographically, it offers a rich amalgamation of the urban and the rural; while the urban is an eclectic mix of regions and religions, the rural is still rooted in folkloric traditions. One such tradition is Dev Uthan Ekadashi: celebrated around ten days after Diwali, it marks the awakening of Lord Vishnu from his four-month long sleep, which symbolises a fresh beginning to the Hindu wedding season. To mark the occasion, this cosmopolitan city’s Haryanvi Hindu women gather to create illustrations, sing folksongs, and perform several rituals. In this paper we examine Gurugram as a site of translation by analysing data collected through two sessions of ethnographic fieldwork, conducted in November 2021 and November 2022. We investigate the relationship between the ritual and the space, both of which, we argue, undergo translation; furthermore, we posit that the women performing the ritual become cultural agents within a postcolonial space. Thus, our study establishes Gurugram as a translational city, demonstrating resistance where the folkloric tradition is kept alive through cultural meanings shaped by language interaction.